Occurrence frequency of rhetorical moves in introductions of linguistics research articles from non-scopus and scopus journals - Geng, Hui; Lee, Geok Imm; Jalaluddin, Ilyana; Tan, Helen (Academy Publication, 2023)
Serving as a fundamental opening section, the research article introduction (RAI) provides an entrance to a certain topic in the exploration of the unknown content of the research. It is a manifestation of rhetorical maneuver and establishes the context, identifies the challenges, and outlines the rationale for the study. Therefore, it is vital to make a well-crafted RAI to catch readers’ attention. However, the disparities in rhetorical moves employed in English linguistics RAIs between non-Scopus-indexed and Scopus-indexed journals have received less scrutiny. The present study aims to investigate the rhetorical move structures in both types of corpora. The non-Scopus and Scopus corpus each contained 50 RAIs. Based on the adapted Swales’ (1990) Create-A-Research-Space (CARS) model, the occurrence frequency of moves and steps was first analyzed, and the relationship between the frequency of moves and steps and the indexing of journals was then explored. The findings showed that the most frequent move in both corpora was Move 1, followed by Move 3 and Move 2. However, the higher number of overall moves in the non-Scopus corpus suggested that there was an overuse of moves by the less experienced writers, and through Chi-square, Move 3 Step 1B (announcing present research) was detected to have a significant relationship with the indexing of journals. The findings of this study pave the way for writers to construct well-organized RAIs and get their papers published in the field of linguistics.